ANALISIS FRAMING PRABOWO SUBIANTO SEBAGAI CAPRES “GEMOY” PADA PILPRES 2024 DI DETIK.COM - Handayani, Hesty; Nurliah; Purwanti, Silviana; WS, Johantan Alfandoa (Fakultas Ilmu Komunikasi Universitas Teknologi Sumbawa, 2025)
In the 2024 presidential election, many interesting things happened, one of which was Prabowo's new image as a cool presidential candidate who succeeded in attracting the attention of the public, especially young voters. This gemoy narrative, which was previously just a joke, has turned into a light political approach in the eyes of the public. This cannot be separated from the role of the media in framing this narrative and then constructing it and becoming a reality, one of which is the online media Detik.com. This research was conducted to show Detik.com's potential bias in reporting gemoy narratives in three news stories that show three social processes according to Berger & Luckman, namely externalization, objectification and internalization using an interpretive qualitative approach. The analysis was carried out using Zhondan Pan & Kosicki's framing analysis which consists of 4 structures, namely syntax, script, thematic and rhetorical. The results of the research show that Detik.com took sides in reporting on Prabowo. This can be seen from the way Detik.com frames the news in a positive direction by building a narrative based on the reporter's perspective without citing sources in news 1 & 2, whereas in news 3 almost the entire narrative is built based on source quotes from the Prabowo-Gibran campaign team. so that the reporting becomes unbalanced and seems biased. In this case, Detik.com also uses indirect quotations to direct the reader's focus to the points it wants to highlight. From this research, Detik.com not only shows partiality but also shows how the media can influence public perception. Keywords: Framing Analysis, Prabowo Subianto, Capres Gemoy, Online Media, Construction of Social Reality